Risk factors associated with positive surgical margins’ location at radical cystectomy and their impact on bladder cancer survival - Claps, Francesco; Van De Kamp, Maaike W.; Mayr, Roman; Bostrom, Peter J.; Boormans, Joost L.; Eckstein, Markus; Mertens, Laura S.; Boeve, Egbert R.; Neuzillet, Yann; Burger, Maximilian; Pouessel, Damien; Trombetta, Carlo; et al. (World Journal of Urology, 2021)
Purpose: To evaluate the risk factors associated with positive surgical margins' (PSMs) location and their impact on disease-specific survival (DSS) in patients with bladder cancer (BCa) undergoing radical cystectomy (RC). Methods: We analyzed a large multi-institutional cohort of patients treated with upfront RC for non-metastatic (cT1-4aN0M0) BCa. Multivariable binomial logistic regression analyses were used to assess the risk of PSMs at RC for each location after adjusting for clinicopathological covariates. The Kaplan–Meier method was used to estimate DSS stratified by margins’ status and location. Log-rank statistics and Cox’ regression models were used to determine significance. Results: A total of 1058 patients were included and 108 (10.2%) patients had PSMs. PSMs were located at soft-tissue, ureter(s), and urethra in 57 (5.4%), 30 (2.8%) and 21 (2.0%) patients, respectively. At multivariable analysis, soft-tissue PSMs were independently associated with pathological stage T4 (pT4) (Odds ratio (OR) 6.20, p < 0.001) and lymph-node metastases (OR 1.86, p = 0.04). Concomitant carcinoma-in-situ (CIS) was an independent risk factor for ureteric PSMs (OR 6.31, p = 0.003). Finally, urethral PSMs were independently correlated with pT4-stage (OR 5.10, p = 0.01). The estimated 3-years DSS rates were 58.2%, 32.4%, 50.1%, and 40.3% for negative SMs, soft-tissue-, ureteric- and urethral PSMs, respectively (log-rank; p < 0.001). Conclusions: PSMs’ location represents distinct risk factors’ patterns. Concomitant CIS was associated with ureteric PSMs. Urethral and soft-tissue PSM showed worse DSS rates. Our results suggest that clinical decision-making paradigms on adjuvant treatment and surveillance might be adapted based on PSM and their location.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Bladder; Cancer; Cystectomy; Margin; Soft tissue; Ureter; Urethra; Urothelial carcinoma